PD-1/PD-L1: A NOVEL TARGET FOR IMMUNOTHERAPY IN PATIENTS WITH NON-SMALL CELL LUNG CANCER - Savić, Ivana; Oprić, Dejan (Medicinski podmladak, 2018)
Immune checkpoints are receptor-ligand interactions that either enhance or turn down the activation of T-lymphocytes. Among them, the interaction of Programmed death receptor-1 (PD-1) and Programmed death ligand-1 (PD-L1) shows suppressive effect of T-lymphocytes, preventing overactivation of T-lymphocytes in inflammation. However, some tumor cells can also express PD-L1 and use it as a strategy to escape the host’s immune response, by binding to PD-1 on T-lymphocytes and inducing their anergy and apoptosis. Hence, a promising approach in cancer therapy would be focused on preventing the tumor cells’ PD-L1 from binding to PD-1 of immune cells by application of monoclonal antibodies against either PD-1 or PD-L1. These novel drugs are known as PD-1/PD-L1 inhibitors, and have been tested in patients with non-small cell lung cancer (NSCLC), particularly in advanced stages of the disease. Compared to conventional chemotherapy, PD-1/PD-L1 inhibitors showed fewer adverse effects, and presented encouraging results in terms of improved survival of NSCLC patients mostly when used as a second line therapy. The therapeutic agents that inhibit PD-1/PD-L1 binding will have a major clinical value if tumor cells express PD-L1 on their membranes. Therefore, reliable interpretation of PD-L1 expression in tumors is needed for optimal selection of patients who would benefit from PD-1/PD-L1 inhibitors. However, PD-L1 as a biomarker needs further improvement, since the estimation of PD-L1 expression is dependent on several factors, such as number of analyzed tumor cells, used antibody, cut-off values.